Improvement of Ablution Skills Through the Practice Methode (Drill) - Ananda Bunga Mutiara Dani Nasution; Imam Tabroni; Murphy Xavier; Mccarty Elliot (Yayasan Adra Karima Hubbi, 2023)
Background. Ablution is an order from Allah Swt written in the Qur'an as a way of purifying before carrying out all kinds of worship including prayer and reading the Qur'an. Purpose. Ablution itself contains two aspects of cleanliness, namely physical cleanliness in the form of washing human body parts, and inner cleanliness caused by the effect of ablution on humans in the form of cleansing from the mistakes of sins committed by body members. Method. The design used by researchers in conducting this research is class action research. In this study using the form of teachers as researchers, where teachers play a very important role in the process of classroom action research. Results. In this form, the main purpose of PTK is to improve learning practices in the classroom. teachers are directly involved in the process of planning, action, observation, and reflection.The results of the analysis in each cycle show that the class average value has increased from 53 in the pre-cycle learning outcomes to 65 in cycle I, then increased to 80 in cycle II. Conclusion. So, the application of the drill method can improve the ablution skills of class VIII students of MTsN 1 Purwakarta. The increase in learning outcomes during learning activities through the drill method shows that students are more motivated when they are directly involved in teaching and learning activities